2007
DOI: 10.7589/0090-3558-43.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Costs of Rabies Exposure: A Retrospective Study in Southern California (1998–2002)

Abstract: The direct and indirect costs of suspected human rabies exposure were estimated for San Luis Obispo and Santa Barbara counties, California, USA. Clinic, hospital, and county public health records (1998-2002) were examined to determine direct costs for postexposure prophylaxis (PEP), and 55 (41%) former patients were contacted to voluntarily provide estimates of their indirect costs associated with receiving PEP. Additional costs due to public health and animal control personnel responses to rabid animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 7 publications
1
56
0
Order By: Relevance
“…This highlights the critical prevention message of having cats vaccinated and of avoiding stray cat exposure, to eliminate the risk of rabies as well as the expense associated with testing and postexposure prophylaxis. The costs associated with preventing rabies are substantial Chang et al, 2002;Shwiff et al, 2007). Raccoon rabies spread across Massachusetts from two distinct foci of introduction in 1992, one in the northcentral part of the state and one in the extreme southwestern corner, as shown in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the critical prevention message of having cats vaccinated and of avoiding stray cat exposure, to eliminate the risk of rabies as well as the expense associated with testing and postexposure prophylaxis. The costs associated with preventing rabies are substantial Chang et al, 2002;Shwiff et al, 2007). Raccoon rabies spread across Massachusetts from two distinct foci of introduction in 1992, one in the northcentral part of the state and one in the extreme southwestern corner, as shown in Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Because rabies patients die quickly, and there is no effective therapy, the cost of illness is relatively small, especially in the developing world. In contrast, the major direct costs arising from factors such as PEP and livestock deaths have been characterized in numerous studies (Shwiff et al, 2007;Sterner et al, 2009;Zinsstag et al, 2009 ). Canine rabies also has indirect costs, including vaccination of livestock and companion animals and testing of dogs suspected of rabies (Anderson et al, 2012;Narrod et al, 2012 ).…”
mentioning
confidence: 94%
“…Each year, rabies is ruled out in more than 99,000 of the animals submitted for testing. A previous study 29 suggested that the average cost of collecting and testing an animal for rabies virus infection was approximately $400. This would place the national costs for laboratory-based rabies surveillance at approximately $45 million annually.…”
Section: Discussionmentioning
confidence: 99%